Development and Validation of HPLC-DAD Method for Simultaneous Determination of Seven Food Additives and Caffeine in Powdered Drinks - Imanulkhan (Foods, 2020)
The usage of food additives must respect the general legislation in force in the country and requires a reliable analytical method for surveillance. This research aimed to develop a high-performance liquid chromatography with diode array detection (HPLC-DAD) method for the simultaneous determination of seven food additives and caffeine in powdered drinks. Three factors likely to affect the chromatographic separation, namely, mobile phase composition at the beginning (x1, 0–10% of the amount of methanol in the phosphate buffer) and the end (x2, 60–100% of the amount of methanol in the phosphate buffer) of the gradient program and pH (x3, 3–7), were evaluated with the aid of a Box–Behnken Design (BBD). Subsequently, multi-response optimizations for chromatographic resolutions (Rs) and analysis time were performed using the response surface methodology (RSM) in conjunction with the desirability function (DF). Complete separation (Rs > 1.5) of seven food additives and caffeine was achieved in less than 16 min by applying 8.5% methanol in the phosphate buffer at the beginning and 90% at the end of the gradient program, in pH 6.7. The developed method was validated with low limits of detection (ranging from 1.16 mg kg−1 (sodium saccharin) to 3.00 mg kg−1 (acesulfame potassium)), low limits of quantification (ranging from 3.86 mg kg−1 (sodium saccharin) to 10.02 mg kg−1 (acesulfame potassium)), high precision (CV < 4%), and high accuracy (recoveries from 95 to 101% at 80, 100, and 120% of the target concentration). The method was successfully used to assess the seven food additives and caffeine in commercially available powdered drinks.